ANALISIS KECELAKAAN LALU LINTAS PADA RUAS JALAN ARTERI PRIMER (STUDI KASUS JALAN MAOSPATI – SOLO, SEGMEN 28.029, STA 11 +020 – 18+020) - Aditya Kurniawan; Dinda Ayu Septiana; Kami Hari Basuki; Amelia Kusuma Indriastuti (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Maospati Highway in Solo is one of the main roads in the East Java Province, considered as accident-prone. As a national road and primary artery, this road has an important role in the distribution of goods and services both intra and interprovincial. The type of highway is 4/2 UD with 11 meters width. The aim of this study is to determine which areas are considered as the accident-prone areas or blacksite, the factors cause the accidents, and suggest some prevention recommendations. The necessary data is the LHR data obtained from the Department of Public Works Binamarga East Java province and traffic accidents data of Police Magetan, east java. Blacksite analysed by method based on accident rates path length LQ and intersection LQ, and the Accident Rate. Based on the analysis, it is conluded that blacksite occurred in the village of Malang, with a value of LQ> 1, and Accident Rate exceeded the upper limit value. The dominant factor causes the accidents is human factor, such as lack of anticipation when driving. The recommendations suggested for the location are the provision of signs, rumble strips and other safety facilities.